Precursor‐Based Synthesis of Porous Colloidal Particles towards Highly Efficient Catalysts. Issue 41 (14th May 2018) - Zheng, Yun; Geng, Hongbo; Zhang, Yufei; Chen, Libao; Li, Cheng Chao
Abstract: In recent years, porous colloidal particles have found promising applications in catalytic fields, such as photocatalysis, electrocatalysis, industrial and automotive byproducts removal, as well as biomass upgrading. These applications are critical for alleviating the energy crisis and environmental pollution. Porous colloidal particles have remarkable specific areas and abundant reactive sites, which can significantly improve the mass/charge transport and reaction rate in catalysis. Precursor‐based synthesis is among the most facile and widely‐adopted methods to achieve monodisperse and homogeneous porous colloidal particles. In the current review, we briefly introduce the general catalytic applications of porous colloidal particles. The conventional precursor‐based methods are reviewed to design state‐of‐the‐art porous colloidal particles as highly efficient catalysts. The recent development of porous colloidal particles derived from metal‐organic frameworks (MOFs), glycerates, carbonate precursors, and ion exchange methods are reviewed. In the end, the current concerns and future development of porous colloidal particles are outlined. Abstract : Catalyst review : In recent years, porous colloidal particles have found promising applications in catalytic fields. The conventional precursor‐based methods are reviewed for the design of state‐of‐the‐art porous colloidal particles as highly efficient catalysts.